Notes on Rafflesia hasseltii Suring. (Rafflesiaceae), a new record for Sarawak, Malaysia - Aida Shafreena, Ahmad Puad; Wan Nuur Fatiha, Wan Zakaria; Connie, Geri; Ramlah, Zainudin; A., LATIFF (Malaysia Nature Society, 2020)
The genus Rafflesia R. Br. (Rafflesiaceae) is a holoparasitic plant with about 37 species recorded and distributed in Southeast Asia (Nais, 2001; Susatya et al., 2006; Sofiyanti et al., 2007; Barcelona et al., 2009a; Barcelona et al., 2009b; Balete et al. 2010; Wiriadinata and Sari, 2010; Barcelona et al., 2011; Haji Adam et al., 2013; Haji Adam et al., 2016; Sofiyanti et al., 2016; Susatya et al., 2017). From the total species recorded, eight species occur in Borneo (Nais, 2001). Rafflesia keithii Meijer, R. pricei Meijer and R. tengku-adlinii Mat Salleh & Latiff occur in Sabah, while the little-known R. borneensis Koord., R. ciliata Koord., R. witkampii Koord., R. hasseltii Suring. and possibly R. arnoldii R. Br. are found in Kalimantan. Only one species occurs in Brunei namely R. pricei while three species are found in Sarawak namely R. pricei, R. keithii, and R. tuan-mudae Becc. The occurrence of R. arnoldii in Sarawak and East Kalimantan could not be confirmed as it could be mistakenly reported by Nais (2001). In records, R. arnoldii occurs in Sumatera, Indonesia (Nais, 2001; Bendiksby et al., 2010). All members of this genus are obligate parasites, rootless and lack chlorophyll, thus they are dependent on various host plants for water, nutrients and survival (Nais, 2001). Currently, a total of 12 Tetrastigma (Miq.) Planch. (Vitaceae) species have been reported as the host plants for Rafflesia species, namely T. curtisii (Ridl.) Suesseng., T. diepenhorstii (Miq.) Latiff, T. glabratum (Blume) Planch., T. scariosum (Miq.) Planch., T. loheri Gagnep., T. harmandii Planch., T. scortechinii (King) Gagnep., T. hookeri (Laws.) Planch., T. pisicarpum (Miq.) Planch., T. cf. magnum Merr., T. papillosum (Blume) Planch. and T. rafflesiae (Miq.) Planch. (Niyomdham & Kubat, 1987; Meijer, 1997; Latiff and Mat-Salleh, 2001; Nais, 2001; Barcelona et al., 2006; Barcelona et al., 2009b; Mokhtar et al., 2016; Wan Zakaria et al., 2016; Wicaksono et al., 2017).